Green growth and innovation in the Global South: a systematic literature review - Herman, Kyle S. (Innovation and development, 2023)
There has been much interest in green growth and innovation in recent years. The main idea is that domestic green growth policies can provide 'win-wins' to both the environment and the economy. But we still know very little about the impact of such policies, especially in developing countries-the 'Global South.' The literature remains underdeveloped. This is disappointing since the Global South could leverage green growth policies to enhance competitiveness, 'leapfrog' directly to cleaner technologies, and 'catch-up' economically and environmentally through innovation in environmental technologies. The lack of research is also problematic because greenhouse gas emissions from developing countries are growing rapidly. Without green growth and innovation it will be exceedingly difficult to meet the urgent needs of climate change. Against this backdrop, this paper conducts machine-aided citation, bibliometric, and keyword analyses on green growth research with a particular focus on developing countries, innovation, and environmental technologies.